The Effect of Menopause Counseling by Counselor Midwives on Attitude and Reduction of Menopause Symptoms in Menopausal Mothers - Ervin Rufaindah; Raden Tina Dewi Judistiani; Ahmad Rizal; Tita Husnitawati Madjid; Tuti Wahmurti; Farid Husin (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
Eighty percent (80%) of women complaint headache, sexual problem, tachycardia, hot flushes and insomnia, that are significantly decrease the quality of life. Objective of the research is to analyze how much the effect of menopause counseling from counselor midwife towards the attitude of menopause women and reduction of the symptoms. The study is quasi experiment with pre and post design. The samples were 40 respondents that were divided into two groups; 20 respondents were in intervention group who were given counseling from counselor midwife and 20 respondents were in control group that were given counseling from non counselor midwife. In each group counseling was given twice at intervals of 2 weeks, long counseling per client requirements. Measurement posttest mother's attitude menopause and the symptoms of menopause mother performed 4 weeks after the pretest. The instruments employed were MAMES (Multi-dimensional Attitudes Menopause Scale) questionnaire for measuring the attitude of menopause women and MRS (Menopause Rating Scale) questionnaire for measuring the symptoms experienced by menopause women. Non parametric and RR value were performed for statistical test. The result of study indicated that the attitude, the mother menopause who did not receive counseling by a midwife counselor, the risk of having a negative attitude 7 times compared with mothers who received counseling by a midwife counselor (RR 7.0). While menopause mothers who did not receive counseling by a midwife counselor, 2.5 times the risk of having symptoms degree rise or stay when compared with mothers who received counseling by a midwife counselor (RR 2.5). Based on the study, it was concluded that there was effect of counseling from counselor midwife towards the improvement of attitude of menopause women and decrease of menopausal symptoms.